CORRELATION BETWEEN SPEED AND OXYGEN CONSUMPTION (VO2) IN RATS SUBMITTED TO MAXIMUM EXERCISE TEST. (Fiep Bulletin - online, 2015)
The objective of the present study was to investigate the correlation between the speed during maximum exercise test (ET) and the consumption of oxygen (VO2) in normal rats. Male Wistar rats (n=8) were submitted a maximal exercise capacity evaluation with gases analyses measurements using a respirometry system. Maximum VO2 and VO2 reserve were 80±2 and 47±2 ml/Kg/min in normal rats.  There was a positive correlation between ET speed and VO2 (r=0.8) in studied animals. Linear regression analysis was used to obtain the equation for the correlation between ET and VO2 (VO2= 1,55 * speed ET + 52.34). The 50% and 85% of the maximum speed of ET was calculated from these equations and it corresponded to 68% and 95% of VO2 reserve, respectively. The maximum speed of ET was correlated with maximum VO2 (r=0.7). Conclusion: 1) VO2 can be estimated by using linear regression equations obtained from correlations between VO2 and ET in control animals; 2) the correlation obtained between ET speed and VO2 demonstrates that physical training prescriptions based on ET in normal rats is adequate 3) the improvement of aerobic performance can be detected by ET since maximum speed was correlated with maximum VO2 among the animals studied.
Keywords: effort test; oxygen consumption; rats.